2017
DOI: 10.3847/1538-4357/aa7e7d
|View full text |Cite
|
Sign up to set email alerts
|

Are Complex Magnetic Field Structures Responsible for the Confined X-class Flares in Super Active Region 12192?

Abstract: From 2014 October 19 to 27, six X-class flares occurred in super active region (AR) 12192. They were all confined flares and were not followed by coronal mass ejections (CMEs). To examine the structures of the four flares close to the solar disk center from October 22 to 26, we employ firstly composite tripletime images in each flare process to display the stratified structure of these flare loops. The loop structures of each flare in both lower (171Å) and higher (131Å) temperature channels are complex, e.g., … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…The average orientation of the PIL is determined from the HMI LOS magnetogram prior to the flare onset. The inclination angle θ corresponds to the angle between the tangents of the PFL and PIL at their intersection (panel (b)), which is consistent with the method of Zhang et al (2017). The complementary angle of θ has been referred to as the shear angle in previous studies (Su et al 2007;Aulanier et al 2012).…”
Section: Resultssupporting
confidence: 69%
“…The average orientation of the PIL is determined from the HMI LOS magnetogram prior to the flare onset. The inclination angle θ corresponds to the angle between the tangents of the PFL and PIL at their intersection (panel (b)), which is consistent with the method of Zhang et al (2017). The complementary angle of θ has been referred to as the shear angle in previous studies (Su et al 2007;Aulanier et al 2012).…”
Section: Resultssupporting
confidence: 69%
“…This result is similar to the earlier finding by Cheng et al (2011) where they did a comparative study of the critical decay index (1.5) height for the onset of the torus instability over both the eruptive and non-eruptive regions belonging to same AR (NOAA AR 10720). Although our study suggests the importance of the background magnetic field strength for the confined behavior of the non-eruptive flares, a recent study (Zhang, Li, and Chen, 2017) reveals that the complex flare loops associated with the non-eruptive flares originating from AR 12192 may also be responsible for the confinement.…”
Section: Discussionmentioning
confidence: 78%
“…Similar results were also documented in Chen et al (2015), where the mean decay index of the horizontal background field was found to be less than the typical threshold required for the torus instability (Kliem & Török 2006) to set in. An alternative explanation was provided by Zhang et al (2017) who attributed the confined nature to the complexity of the involved magnetic field structures.…”
Section: Discussion On the X31 Flare Eventmentioning
confidence: 99%